2009
DOI: 10.1007/s10750-009-9780-2
|View full text |Cite
|
Sign up to set email alerts
|

Base-line variations in stable isotope values in an Arctic marine ecosystem: effects of carbon and nitrogen uptake by phytoplankton

Abstract: Stable isotope values are useful for elucidating C and N cycling and pathways in marine and aquatic ecosystems. Variations in the base-line isotope values, the d 13 C and d 15 N values of phytoplankton, put constraints on their usefulness as tracers for trophic interactions and sources of organic matter in food web studies, however. We investigated the C and N stable isotope values of suspended particulate organic matter in relation to uptake of total dissolved inorganic carbon and nitrate, chlorophyll a conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 58 publications
5
45
0
Order By: Relevance
“…We analyzed potential sources of this variability by examining diets, oceanographic conditions and fish migration. Diet shifts with size do not account for the variability, but the utilization, differences in nutrient sources (e.g., denitrification vs. N 2 fixation) and the subsequent biological transformations of these nutrients (Altabet 2001, Sigman and Casciotti 2001, Tamelander et al 2009Graham et al 2010;Carlisle et al 2012). The δ 15 N and δ 13 C values of an organism alone provide little information about its ultimate trophic position, and it is essential that ratios are compared to an appropriate baseline (Post 2002;Borrell et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed potential sources of this variability by examining diets, oceanographic conditions and fish migration. Diet shifts with size do not account for the variability, but the utilization, differences in nutrient sources (e.g., denitrification vs. N 2 fixation) and the subsequent biological transformations of these nutrients (Altabet 2001, Sigman and Casciotti 2001, Tamelander et al 2009Graham et al 2010;Carlisle et al 2012). The δ 15 N and δ 13 C values of an organism alone provide little information about its ultimate trophic position, and it is essential that ratios are compared to an appropriate baseline (Post 2002;Borrell et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The ratios of 13 C/ 12 C in dissolved inorganic carbon (bicarbonate) and primary production are conserved as energy is transferred through the food web, providing an indicator of energy source and habitat (Hobson et al, 2002;Tamelander et al, 2009). Conversely, the relative trophic position of aquatic species can be inferred based on stepwise trophic enrichment in tissue 15 N from the base of the food web (Hobson et al, 2002;Minagawa and Wada, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In short, the baseline shifts appeared to explain most of the spatial variation in δ Baseline isotope values are influenced by the physical and biological properties of local currents (Pantoja et al 2002), terrestrial input (Carlier et al 2007) and species composition and bloom progression (Tamelander et al 2009). The combined effect of these direct and indirect factors on primary producers will propagate up the food web, influencing the isotopic signatures of all trophic levels, though with diminishing strength towards higher trophic levels.…”
mentioning
confidence: 99%
“…showed that rising temperature can have a negative effect on δ Whether these factors cause the differences in δ 15 N values remains unknown, as other undocumented factors such as changes in the composition of primary production or seasonal progression could result in similar variation (Tamelander et al 2009). …”
mentioning
confidence: 99%